Formulation and Evaluation of Bioactive Gelatin from Tilapia (Oreochromis niloticus) Scales as an Antioxidant-Based Anti-Aging Cream - Herlina Herlina; Suci Wulandari; Barita Aritonang; Amelia Putri Eflynia; Lasmaryna Sirumapea (Jurnal FARMASIMED (JFM), 2026)
The increasing demand for sustainable, bioactive cosmetic ingredients has driven the use of marine by-products as alternative raw materials. Tilapia (Oreochromis niloticus) scales, an abundant aquaculture waste, are rich in collagen that can be converted into gelatin with potential dermatological applications. This study aimed to develop and evaluate bioactive gelatin derived from tilapia scales as an antioxidant-based anti-aging cream. Gelatin was extracted with 15% acetic acid and characterized by physicochemical parameters, including yield (4.6%), moisture content (12%), and ash content (2.2%), all of which met SNI standards. Antioxidant activity was determined using the DPPH method, yielding an IC₅₀ value of 139.46 ppm, indicating moderate to weak antioxidant activity. The gelatin was formulated into cream preparations at concentrations of 1%, 1.5%, and 2%, and the formulations were evaluated for stability, homogeneity, pH, spreadability, and irritation. Anti-aging efficacy was assessed using a skin analyzer, showing improvements in skin moisture and sebum balance, with the 1% formulation demonstrating optimal performance. Although the antioxidant activity was relatively low, topical application of gelatin contributed to measurable anti-aging effects. These findings highlight the potential of tilapia scale-derived gelatin as a sustainable bioactive ingredient for cosmeceutical applications.